A computational framework for selecting the optimal combination of seismic retrofit and insurance coverage. (20th October 2021) - Gentile, Roberto; Pampanin, Stefano; Galasso, Carmine
Abstract: Economic earthquake losses can be mitigated through either building retrofit strategies and/or, to some extent, risk‐transfer to the (re)insurance market. This paper proposes a computational framework to select the optimal combination of seismic retrofit and insurance policy parameters for buildings. First, a designer selects a suitable retrofit strategy. This is implemented incrementally to define interventions with increasing retrofit performance levels. The cost of each intervention is calculated, along with the cost of property rental while the retrofit is implemented. Alternative insurance options are considered. For each retrofit‐insurance combination, the insured and uninsured economic losses within a given time horizon are estimated. The optimal retrofit and insurance combination minimizes the tail value at risk of the life cycle cost. The selected confidence level for this metric depends on the homeowner's risk aversion. The proposed framework is illustrated for a case‐study archetype Italian reinforced concrete frame building retrofitted with concrete jacketing, also considering the Italian retrofit tax incentives/rebates called " Sismabonus ."